2021
DOI: 10.1002/open.202000357
|View full text |Cite
|
Sign up to set email alerts
|

Metal Sulfide Nanoparticle Synthesis with Ionic Liquids – State of the Art and Future Perspectives

Abstract: Metal sulfides are among the most promising materials for a wide variety of technologically relevant applications ranging from energy to environment and beyond. Incidentally, ionic liquids (ILs) have been among the top research subjects for the same applications and also for inorganic materials synthesis. As a result, the exploitation of the peculiar properties of ILs for metal sulfide synthesis could provide attractive new avenues for the generation of new, highly specific metal sulfides for numerous applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 239 publications
(504 reference statements)
0
15
0
Order By: Relevance
“…The chemistry of chalcogens and metal chalcogenides in ILs is manifold and gained a lot of interest in recent years. 1,4,6,22–26 Boros et al showed the dissolution of non-metallic solid elements in ILs, in particular the dissolution of sulfur in trihexyltetradecylphosphonium decanoate, [P 66614 ][dec], in which sulfur is highly soluble. The dissolved sulfur species shows a concentration dependency between [S 3 ]˙ − and [S 6 ] 2− , were the latter one occurs at higher concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of chalcogens and metal chalcogenides in ILs is manifold and gained a lot of interest in recent years. 1,4,6,22–26 Boros et al showed the dissolution of non-metallic solid elements in ILs, in particular the dissolution of sulfur in trihexyltetradecylphosphonium decanoate, [P 66614 ][dec], in which sulfur is highly soluble. The dissolved sulfur species shows a concentration dependency between [S 3 ]˙ − and [S 6 ] 2− , were the latter one occurs at higher concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,27–30 Among them, the most prominent compound contains the supersphere anion [Ge 24 Sn 36 Se 132 ]. 24–31,32 But also a new modification of K 2 Sn 2 S 5 was accessible, which obviously does not include the IL used. 33…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been stated that “ILs have advantages (or shall we say, different properties that may be useful) compared to conventional liquid phase synthesis.” [255] A similar statement can be made for ILCs. Like ILs, ILCs have very interesting and potentially useful properties such as high ionicity or anisotropic ionic conduction while maintaining a very stable supramolecular architecture, often over a rather large temperature window or at temperatures where other LCs may not perform well.…”
Section: Future Perspectives and Challengesmentioning
confidence: 71%
“…In spite of this, there are precedents. Details have been discussed in a previous article [255] but it is worthwhile to highlight a study by Jean et al. on the obstacles for commercialization of quantum dots (QDs) [268] because many of the arguments made there can also be applied to the commercialization of ILCs.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…The use and application studies of metal sulfide nanoparticles (NPs) have increased in several fields, such as biomedicine, environmental remediation, agriculture, electronics, and catalytic reactions [60], as well as diverse applications such as surface coating, nanoswitches, solar cell components, radiation absorbers, photocatalysts, gas sensors, and dielectric filters [103]. Likewise, several routes for the synthesis of metal sulfide NPs have been proposed [104], even using ionic liquids [105]. In this context, there is an interesting opportunity to produce metal sulfide NPs directly from wastewaters or industrial solutions using a metal sulfide precipitation process.…”
Section: Nanoparticle Productionmentioning
confidence: 99%